Geopolitical Conflict between Great Powers in the 21st Century: an Analysis of the Ukraine Crisis - Le Hoang Kiet; Tran Xuan Hiep (Современная Европа)
The Ukrainian crisis is not just an armed conflict between two nations, but also reflects the geopolitical competition between great powers in the 21st century. This paper will analyze the deep-rooted origins leading to the military conflict through a geopolitical lens, delving into the long process of historical tensions and confrontation between Russia and the West represented by the North Atlantic Treaty Organization (NATO) regarding the issue of Ukraine. The study will explore Russia’s geostrategic motives in starting special military operation in Ukraine, NATO’s efforts to expand its influence into this region, as well as the complex developments that caused the conflict to escalate into the largest armed war since the beginning of the 21st century. Through this, the paper analyzes the profound nature of the geopolitical crisis in Ukraine in the context of the power struggle between major powers in this strategic region; provide a comprehensive view of the motives, strategies of the parties involved, as well as the far-reaching implications this conflict has caused for security in the European region. In doing so, it contributes to a better understanding of the complex nature of geopolitical conflict and security in the 21st century.